DIFFERENCE OF MODERATE AND HARD-BRISTLED TOOTHBRUSH IN PREVENTING PLAQUE AMONG SCHOOL CHILDREN - Karsum Udin; Bedjo Santoso; Ida Rahmawati; Emilda Sari; Dedy Dedy (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Oral health is very important, some oral and dental problems occur because we do not maintain oral hygiene and teeth. Plaque is a major etiologic factor of caries and periodontal disease. Efforts to prevent plaque buildup is called plaque control, by mechanical, chemical and natural, mechanical ventilation is a tooth brush. In general, the bristles are soft, moderate, and hard. Aims: This research aims to know the differences using a moderate and hard-bristled toothbrush againstplaque. Methods: This is a quasi-experiment with pretest-post-test control group design between the bristles medium and hard bristles using independent test T-test. Results: Independent t-test for hard toothbrush has an average value of 2.08 decrease in the number of plaques, while the toothbrush being has an average value of 1.35 decrease in the amount of plaque. The pvalue (0.000) <α (0.05), no difference using a toothbrush moderate and hard-bristled against plaque. Conclusion: There is a difference of tooth brushing plaque by using the medium tough and hairbrush medium tough hairbrush and hairy on the students of class VII B and VII C in Public Junior High School 3 Banjarbaru. The use of hard bristled toothbrushes is better 72.22% than the use of medium toothbrushes is only 47.37%. But a hard hairy toothbrush can cause gums to drop (recession gingival) if done continuously.